2023
DOI: 10.1038/s41524-023-01024-5
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling effects of electron correlation in two-dimensional FenGeTe2 (n = 3, 4, 5) by dynamical mean field theory

Abstract: The FenGeTe2 systems are recently discovered two-dimensional van-der-Waals materials, exhibiting magnetism at room temperature. The sub-systems belonging to FenGeTe2 class are special because they show site-dependent magnetic behavior. We focus on the critical evaluation of magnetic properties and electron correlation effects in FenGeTe2 (n = 3, 4, 5) (FGT) systems performing first-principles calculations. Three different ab initio approaches have been used primarily, viz., (i) standard density functional theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 83 publications
5
25
0
Order By: Relevance
“…Formation energies indicate that up to doping concentrations of 20.1%, Co atoms prefer to substitute to the outermost Fe sublattices, i.e., FeU and FeD species (dark blue color). This is compatible with previous results, showing that Fe split sites are most prone to defects. ,, The magnetic anisotropy energy (MAE) of pristine and Co-doped structures in monolayer and bulk forms is listed in Table S2. Note that, in the absence of Co, the pure Fe 5 GeTe 2 (FGT) monolayer has an out-of-plane easy magnetization axis, with MAE = +18.7 μeV/atom.…”
Section: Resultssupporting
confidence: 91%
“…Formation energies indicate that up to doping concentrations of 20.1%, Co atoms prefer to substitute to the outermost Fe sublattices, i.e., FeU and FeD species (dark blue color). This is compatible with previous results, showing that Fe split sites are most prone to defects. ,, The magnetic anisotropy energy (MAE) of pristine and Co-doped structures in monolayer and bulk forms is listed in Table S2. Note that, in the absence of Co, the pure Fe 5 GeTe 2 (FGT) monolayer has an out-of-plane easy magnetization axis, with MAE = +18.7 μeV/atom.…”
Section: Resultssupporting
confidence: 91%
“…As a result of the stronger SOC in heavier Se atoms, Mn 2 Mg 2 Se 5 exhibits a higher MAE. A comparison with monolayers of CrI 3 (%À0.80 meV/Cr), CrBr 3 (%À0.16 meV/Cr), Cr 2 Ge 2 Te 6 (%0.33 meV/Cr), and Fe 3 GeTe 2 (%À1.22 meV/Fe) [11,58,59] shows that Mn 2 Mg 2 Se 5 Table 3. Magnetic properties of Mn 2 Mg 2 X 5 structures, M-Mn and M-X i are the magnetic moments on Mn and X sites (S, Se), respectively, in units of μ B , MAE is the magnetic anisotropy energy in units of meV/Mn, where a positive value indicates easy-plane anisotropy, J 1 , J 2 , and J 3 are first, second, and third neighbor isotropic Heisenberg exchange interactions, respectively, in units of meV, T C-MF and T C-MF are the mean-field and MC magnetic transition temperatures, respectively, in units of K. possess a relatively strong magnetic anisotropy, which is essential for the stabilization of FM order at elevated temperatures and desirable for potential applications in spintronics and magnetic devices.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…The thin films of metallic Fe n GeTe 2 (where n = 3, 4, and 5) exhibit ferromagnetism, close to room temperature. [9][10][11] Moreover, their T C can be further increased via doping. [12] Among them, only Fe 3 GeTe 2 is exfoliated up to 2D regime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we study electronic and magnetic properties of Fe 2 C using the combination of DFT with the dynamic mean field theory (DMFT). Despite the latter theory was originally proposed as a tool of describing high-dimensional strongly-correlated systems [43,44], in recent works it was shown that DFT+DMFT approach significantly better than DFT describes 2D correlated ferromagnetic materials, such as CrI 3 [45,46] and Fe n GeTe 2 [47,48], yielding better agreement with experimental data. Although this approach, in view of its mean-field nature, yields finite Curie transition temperature for isotropic 2D systems, its application to paramagnetic state allows to obtain valuable information on the magnitude of magnetic moments and exchange interactions, which can be used for more accurate calculation of magnetic transition temperatures (see, e.g.…”
Section: Introductionmentioning
confidence: 99%